2017
DOI: 10.1055/s-0037-1607392
|View full text |Cite
|
Sign up to set email alerts
|

Interview Scores Correlate with Fellow Microsurgical Skill and Performance

Abstract: The results of this study, for the first time, validate the current interview process to correctly select the highest performing and most skilled candidates and support the effectiveness of a 1-year microsurgical fellowship in improving microsurgical skill in all trainees, irrespective of their initial ability. The importance of valuing the relative quality of prior training and experience at selection is also highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Also, an additional year of microsurgery fellowship offers more exposure and training in microsurgery after residency, which will subsequently increase expertise in performing microsurgical reconstruction. Numerous studies have demonstrated that microsurgery fellowships help expediate the learning curve and provide the opportunity for additional training microsurgical reconstruction 31–33 . Therefore, as time progresses with increasing the number of graduated plastic surgeons with microsurgical training as well as fellowship trained microsurgeons, we expect to continue to see an increasing incidence in microsurgical ABR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an additional year of microsurgery fellowship offers more exposure and training in microsurgery after residency, which will subsequently increase expertise in performing microsurgical reconstruction. Numerous studies have demonstrated that microsurgery fellowships help expediate the learning curve and provide the opportunity for additional training microsurgical reconstruction 31–33 . Therefore, as time progresses with increasing the number of graduated plastic surgeons with microsurgical training as well as fellowship trained microsurgeons, we expect to continue to see an increasing incidence in microsurgical ABR.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that microsurgery fellowships help expediate the learning curve and provide the opportunity for additional training microsurgical reconstruction. [31][32][33] Therefore, as time progresses with increasing the number of graduated plastic surgeons with microsurgical training as well as fellowship trained microsurgeons, we expect to continue to see an increasing incidence in microsurgical ABR.…”
Section: Discussionmentioning
confidence: 99%
“…These fellowships typically provide a 1-year training experience and, on average, approximately 110 cases for the year (range, 60–180). 53 56 Numerous studies have demonstrated that fellowships help expedite the learning curve. Rather than purely focusing on microsurgery technique, fellowships provide the opportunity for additional training in microsurgical reconstruction.…”
Section: Microsurgery Fellowshipsmentioning
confidence: 99%
“…Furthermore, fellows with lower initial assessments improved their technical abilities more rapidly, whereas fellows with higher initial assessments made their greatest improvement in speed and efficiency. 53 Microsurgery is a highly technical field where high-volume hands-on training was necessary. 54 On a survey of 26 fellows gauging the average comfort level from 1 to 5 on independently performing a deep inferior epigastric perforator (DIEP) free flap, this score rose from 2.7 on the first day of fellowship to 4.8 by the final day.…”
Section: Microsurgery Fellowshipsmentioning
confidence: 99%